Alexandria : a Cultural and Religious Melting Pot. - Hinge, George (Aarhus studies in Mediterranean antiquity., 2010)
Throughout the entire span of Graeco-Roman antiquity Alexandria represented a meeting place for many ethnic cultures and the city itself was subject to a wide range of local developments, which created and formatted a distinct Alexandrine 'culture' as well as several distinct 'cultures'. Ancient Greek, Roman and Jewish observers communicated or held claim to that particular message. Hence, Arrian, Theocritus, Strabo, and Athenaeus reported their fascination of the Alexandrine melting pot to the wider world and so did Philo, Josephus and Clement. In various fashions, the four papers of Part I o.